Biochemical and spectroscopic characterization of photocomplexes from the extremely halophilic purple sulfur bacterium, Halorhodospira halophila strain SL1T - I. Satoh; K. Inada; N. Hiwatashi; S. Ohara; N. Shimazaki; E.R. Purba; T. Mochizuki; A. Mizoguchi; L.-J. Yu; J. Overmann; M.T. Madigan; K. Tani; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2026)

Identifying the stand properties that support both high biodiversity and carbon storage in German forests - K. Springer; P. Manning; A.L. Boesing; C. Ammer; A.M. Fiore-Donno; M. Fischer; K. Goldmann; G. Le Provost; J. Overmann; L. Ruess; I. Schöning; S. Seibold; et al. (Forest Ecology and Management, 2024)

Discovery pipelines for marine resources: an ocean of opportunity for biotechnology? - D. Smith; A. G. Buddie; R. J. M. Goss; J. Overmann; C. Lepleux; M. Brönstrup; B. Kloareg; T. Meiners; P. Brennecke; A. Ianora; F.-Y. Bouget; P. Gribbon; et al. (World Journal of Microbiology and Biotechnology, 2019)

Function of bacterial community dynamics in the formation of cadaveric semiochemicals during in situ carcass decomposition - Javier Pascual; Christian von Hoermann; Ann‐Marie Rottler‐Hoermann; Omer Nevo; Alicia Geppert; Johannes Sikorski; Katharina J. Huber; Sandra Steiger; Manfred Ayasse; Jörg Overmann (Environmental Microbiology, 2017)
Summary The decomposition of dead mammalian tissue involves a complex temporal succession of epinecrotic bacteria. Microbial activity may release different cadaveric volatile organic compounds which in turn attract other key players of carcass decomposition such as scavenger insects. To elucidate the dynamics and potential functions of epinecrotic bacteria on carcasses, we monitored bacterial communities developing on still‐born piglets incubated in different forest ecosystems by combining high‐throughput Illumina 16S rRNA sequencing with gas chromatography‐mass spectrometry of volatiles. Our results show that the community structure of epinecrotic bacteria and the types of cadaveric volatile compounds released over the time course of decomposition are driven by deterministic rather than stochastic processes. Individual cadaveric volatile organic compounds were correlated with specific taxa during the first stages of decomposition which are dominated by bacteria. Through best‐fitting multiple linear regression models, the synthesis of acetic acid, indole and phenol could be linked to the activity of Enterobacteriaceae , Tissierellaceae and Xanthomonadaceae , respectively. These conclusions are also commensurate with the metabolism described for the dominant taxa identified for these families. The predictable nature of in situ synthesis of cadaveric volatile organic compounds by epinecrotic bacteria provides a new basis for future chemical ecology and forensic studies.

217 000‐year‐old DNA sequences of green sulfur bacteria in Mediterranean sapropels and their implications for the reconstruction of the paleoenvironment - Marco J. L. Coolen; Jörg Overmann (Environmental Microbiology, 2007)
Summary Deep‐sea sediments of the eastern Mediterranean harbour a series of dark, organic carbon‐rich layers, so‐called sapropels. Within these layers, the carotenoid isorenieratene was detected. Since it is specific for the obligately anaerobic phototrophic green sulfur bacteria, the presence of isorenieratene may suggest that extended water column anoxia occurred in the ancient Mediterranean Sea during periods of sapropel formation. Only three carotenoids (isorenieratene, β‐isorenieratene and chlorobactene) are typical for green sulfur bacteria and thus do not permit to differentiate between the ∼80 known phylotypes. In order to reconstruct the paleoecological conditions in more detail, we searched for fossil 16S rRNA gene sequences of green sulfur bacteria employing ancient DNA methodology. 540 bp‐long fossil sequences could indeed be amplified from up to 217 000‐year‐old sapropels. In addition, such sequences were also recovered from carbon‐lean intermediate sediment layers deposited during times of an entirely oxic water column. Unexpectedly, however, all the recovered 16S rRNA gene sequences grouped with freshwater or brackish, rather than truly marine, types of green sulfur bacteria. It is therefore feasible that the molecular remains of green sulfur bacteria originated from populations which thrived in adjacent freshwater or estuarine coastal environments rather than from an indigenous pelagic population.

The puf operon of the purple sulfur bacterium Amoebobacter purpureus: structure, transcription and phylogenetic analysis - Christian Tuschak; Molly M. Leung; J. Thomas Beatty; Jörg Overmann (Archives of Microbiology, 2005)

Desulfosporomusa polytropa gen. nov., sp. nov., a novel sulfate-reducing bacterium from sediments of an oligotrophic lake - Henrik Sass; Jrg Overmann; Heike Rtters; Hans-Dietrich Babenzien; Heribert Cypionka (Archives of Microbiology, 2004)

Photosynthesis Genes and LH1 Proteins of Roseospirillum Parvum 930I, a Purple Non-Sulfur Bacterium with Unusual Spectral Properties - Christian Tuschak; J. Thomas Beatty; Jörg Overmann (Photosynthesis Research, 2004)

Phototrophic consortia: model systems for symbiotic interrelations between prokaryotes - Jö rg Overmann; Karin Schubert (Archives of Microbiology, 2002)

Previously unknown and phylogenetically diverse members of the green nonsulfur bacteria are indigenous to freshwater lakes - Frederic Gich; Jesú s Garcia-Gil; Jö rg Overmann (Archives of Microbiology, 2001)

Specific detection of different phylogenetic groups of chemocline bacteria based on PCR and denaturing gradient gel electrophoresis of 16S rRNA gene fragments - J. Overmann; M. J. L. Coolen; Christian Tuschak (Archives of Microbiology, 1999)

Grazing of the copepod Diaptomus connexus on purple sulphur bacteria in a meromictic salt lake - Jörg Overmann; Kenneth J. Hall; Tom G. Northcote; J. Thomas Beatty (Environmental Microbiology, 1999)
A meromictic lake ecosystem (Mahoney Lake, BC, Canada) was investigated to elucidate the significance of chemocline bacteria in the total carbon cycle under natural conditions. In this lake, primary production by oxygenic phototrophs was insufficient to support the observed net secondary production of the calanoid copepod Diaptomus connexus and the rotifer Brachionus plicatilis , indicating the presence of additional food sources for consumers. Mahoney Lake harbours the densest population of phototrophic sulphur bacteria ever reported in a natural body of water. This layer is located at the interface between oxic and anoxic water layers and is dominated by the purple sulphur bacterium Amoebobacter purpureus . The transfer rates of A. purpureus carbon to D. connexus determined in stratified mesocosms were very low (0.71 ngC copepod −1 day −1 ) and accounted for only 0.6% of the observed net biomass increase in the zooplankter. Stable stratification within the mesocosms prevented an upwelling of A. purpureus into the oxic part. However, measurements of carbon fluxes, infrared fluorescence microscopy and stable carbon analysis provided cumulative evidence that, under in situ conditions, the cell carbon of purple sulphur bacteria indeed enters the aerobic food chain via the grazing activity of D. connexus . Based on a two‐source isotopic mixing model, A. purpureus represents at least 75–85% of the diet of D . connexus . Autumnal upwelling into oxic water layers and aggregation of A . purpureus cells appear to be the main factors determining the high carbon flux from purple sulphur bacteria to zooplankton under natural conditions, and most probably also play a key role in other aquatic ecosystems. Through this pathway, over 53% of the reduced organic matter of purple sulphur bacteria trapped in anoxic bottom waters is returned to the oxic realm.

Selective enrichment and characterization of Roseospirillum parvum , gen. nov. and sp. nov., a new purple nonsulfur bacterium with unusual light absorption properties - Jens Glaeser; J. Overmann (Archives of Microbiology, 1999)

Specific detection of green sulfur bacteria by in situ hybridization with a fluorescently labeled oligonucleotide probe - Christian Tuschak; Jens Glaeser; J. Overmann (Archives of Microbiology, 1999)

High genetic and physiological diversity of sulfate-reducing bacteria isolated from an oligotrophic lake sediment - Henrik Sass; Elze Wieringa; Heribert Cypionka; Hans-Dietrich Babenzien; J. Overmann (Archives of Microbiology, 1998)

Physiology and tactic response of the phototrophic consortium " Chlorochromatium aggregatum " - Jürgen M. Fröstl; J. Overmann (Archives of Microbiology, 1998)

The ecological niche of the consortium " Pelochromatium roseum " - J. Overmann; Christian Tuschak; Henrik Sass; J. Fröstl (Archives of Microbiology, 1998)

Phylogeny and molecular fingerprinting of green sulfur bacteria - J. Overmann; Christian Tuschak (Archives of Microbiology, 1997)

Fossil carotenoids and paleolimnology of meromictic Mahoney Lake, British Columbia, Canada - Jrg Overmann; Gerhard Sandmann; Ken J. Hall; Tom G. Northcote (Aquatic Sciences, 1993)

Continuous chemotrophic growth and respiration of Chromatiaceae species at low oxygen concentrations - Jrg Overmann; Norbert Pfennig (Archives of Microbiology, 1992)

A new purple sulfur bacterium from saline littoral sediments, Thiorhodovibrio winogradskyi gen. nov. and sp. nov. - Jrg Overmann; Ulrich Fischer; Norbert Pfennig (Archives of Microbiology, 1992)

Gas vesicle formation and buoyancy regulation in Pelodictyon phaeoclathratiforme (Green sulfur bacteria) - Jrg Overmann; Susanne Lehmann; Norbert Pfennig (Archives of Microbiology, 1991)

Pelodictyon phaeoclathratiforme sp. nov., a new brown-colored member of the Chlorobiaceae forming net-like colonies - Jrg Overmann; Norbert Pfennig (Archives of Microbiology, 1989)

Control of primary productivity and the significance of photosynthetic bacteria in a meromictic kettle lake. Mittlerer Buchensee, West-Germany - Jrg Overmann; Max M. Tilzer (Aquatic Sciences, 1989)